2016
DOI: 10.1111/1556-4029.13194
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Homicide‐Suicides in the United States and Sweden

Abstract: Research on homicides followed by suicides has largely relied on very localized samples and relatively short time spans of data. As a result, little is known about the extent to which patterns within cases of homicide-suicides are geographically specific. The current study seeks to help fill this gap by comparing twenty years of homicide-suicide data for Sweden and a large U.S. county. Although some of the underlying patterns in the two countries are similar (e.g., decreasing rates), a number of important diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
(198 reference statements)
3
16
0
2
Order By: Relevance
“…Not only are victims killed in a private location most likely to be killed by a family member or someone they know (Litwin, 2004), making the number of suspects limited, such homicides are also frequently followed by the suicide of the perpetrator. Prior studies show homicide–suicide rates in Finland and Switzerland to be considerably higher than in other European countries, with rates in Finland ranging from 0.17 to 0.20 per 100,000 (Kivivuori and Lehti, 2003; Saleva et al, 2007) and rates in Switzerland hovering around 0.09 per 100,000 (Liem et al, 2011) compared with rates of 0.07 in Sweden (Regoeczi et al, 2016) and 0.05 per 100,000 (Liem et al, 2011) in the Netherlands, respectively. The relatively high prevalence of homicide–suicide in Finland and Switzerland could partly explain the relatively high clearance rate in these countries compared with the Netherlands and Sweden.…”
Section: Discussionmentioning
confidence: 96%
“…Not only are victims killed in a private location most likely to be killed by a family member or someone they know (Litwin, 2004), making the number of suspects limited, such homicides are also frequently followed by the suicide of the perpetrator. Prior studies show homicide–suicide rates in Finland and Switzerland to be considerably higher than in other European countries, with rates in Finland ranging from 0.17 to 0.20 per 100,000 (Kivivuori and Lehti, 2003; Saleva et al, 2007) and rates in Switzerland hovering around 0.09 per 100,000 (Liem et al, 2011) compared with rates of 0.07 in Sweden (Regoeczi et al, 2016) and 0.05 per 100,000 (Liem et al, 2011) in the Netherlands, respectively. The relatively high prevalence of homicide–suicide in Finland and Switzerland could partly explain the relatively high clearance rate in these countries compared with the Netherlands and Sweden.…”
Section: Discussionmentioning
confidence: 96%
“…The few existing scientific reports on violent crime trends in Sweden show that since the early 1990s there has been an overall decrease in intimate partner homicides (Caman et al 2017), child homicides (Hedlund et al 2016), homicides by individuals with psychosis (Sturup and Lindqvist 2014), homicide-suicide cases (Regoeczi et al 2016) and alcohol-related homicides (Granath 2011). Previous research has also reported that gun modus was the strongest risk factor for not clearing a homicide case .…”
Section: The Trend Of Gun Violence In Swedenmentioning
confidence: 99%
“…The rates of homicide-suicide vary considerably between different countries; the perpetrators of such events are likely to be older than perpetrators of homicide-only cases, and the victims are often female intimate partners (either former or current) (Liem, Barber, Markwalder, Killias, & Nieuwbeerta, 2011;Panczak et al, 2013). In Sweden, a declining incidence of homicide-suicides has been reported for the period 1991-2010 (Regoeczi, Granath, Issa, Gilson, & Sturup, 2016). Since homicide-suicide offenders cannot be interrogated post offense, the circumstances that precede such tragic events are sometimes difficult to disentangle, and police investigators and researchers may have to rely on notes left behind by the perpetrator as the only source of information (Sturup & Caman, 2015;Weeke & Oberwittler, 2017).…”
Section: Homicide-suicidementioning
confidence: 99%